Gambaran Pengetahuan ASI Eksklusif pada Ibu Hamil di Desa Bahari Makmur: Overview of Exclusive Breastfeeding Knowledge on Pregnant Women in Makmur Bahari Village - Siti Adhoat Aristiani; Yulia Nur Khayati (Journal of Holistics and Health Sciences (JHHS), 2022)
Exclusive breastfeeding is very important for the growth and intelligence of baby’s brain. Data on Exclusive breastfeeding in Central Sulawesi Province is still below the nasional Exclusive breastfeeding coverage, which is 61.9%. Based on information obtained at the village midwife Bahari Makmur, Lamala District, Banggai Regency, in 2021 from January to September there were 90% of babies who did not get exclusive breastfeeding, and it was known that babies were given formula milk to replace breast milk and were given additional food in the form of solid food for their babies. before the predetermined time, namely the age of the baby is less than 6 months. The purpose of the study was to describe the knowledge of exclusive breastfeeding in pregnant women in the Bahari Makmur Village. Methods this type of research uses descriptive quantitative with a cross sectional approach. The population in this study were all pregnant women for the September 2021 period with a total of 33 people in Bahari Makmur Village, Lamala District, Banggai Regency, Central Sulawesi Province, using a total sampling technique. The research instrument used a questionnaire and the data analysis used was univariate analysis. Results mothers who have good knowledge are 2 respondents (6.1%) and those who have less knowledge are 21 respondents (63.6%). Conclusion most pregnant women have less knowledge as many as 21 respondents (63.6%). Suggestions for health workers are that health services, especially midwives, are more active in improving health promotion by using media counseling or health education about exclusive breastfeeding such as leaflets or videos so that mothers are more interested and more active in exclusive breastfeeding ABSTRAKASI Eksklusif sangat penting bagi pertumbuhan dan kecerdasan otak bayi. Data pemberian ASI eksklusif di Provinsi Sulawesi tengah masih berada dibawah cakupan ASI Eksklusif nasional yaitu 61,9%. Berdasarkan informasi yang diperoleh di bidan desa Bahari Makmur, Kecamatan Lamala, Kabupaten Banggai tahun 2021 bulan Januari sampai September terdapat 90% bayi yang tidak mendapatkan ASI eksklusif, dan diketahui bayi diberikan susu formula untuk menggantikan ASI serta diberikan makanan tambahan berupa makanan makanan padat pada bayinya sebelum waktu yang telah ditentukan yaitu usia bayi kurang dari 6 bulan. Tujuan penelitian untuk mengetahui gambaran pengetahuan ASI eksklusif pada ibu hamil di Desa Bahari Makmur. Jenis penelitian ini menggunakan deskriptif kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh ibu hamil periode September tahun 2021 sejumlah 33 orang di Desa Bahari Makmur Kecamatan Lamala Kabupaten Banggai Provinsi Sulawesi Tengah dengan menggunakan teknik total sampling. Intrumen penelitian menggunakan kuisioner dan analisis data yang digunakan adalah analisis univariat. Hasil penelitian bahwa ibu yang memiliki pengetahuan baik sebanyak 2 responden (6,1%) dan yang memiliki pengetahuan kurang sebanyak 21 responden (63,6%). Simpulan penelitian ini sebagian besar ibu hamil memiliki pengetahuan kurang sebanyak 21 responden (63,6%). Saran bagi tenaga kesehatan diharapkan pelayanan kesehatan khususnya bidan lebih giat lagi dalam meningkatkan promosi kesehatan dengan menggunakan media penyuluhan atau pendidikan kesehatan tentang ASI eksklusif seperti lefleat atau video agar ibu lebih tertarik dan semakin giat lagi dalam memberikan ASI eksklusif